High Voltage Tolerant Linear Regulator With Fast Digital Control for Biasing of Integrated DC-DC Converters. - Hazucha, P. (IEEE Journal of solid state circuits)
Integrated DC-DC converters switching above 100MHz dramatically reduce the footprint of the inductors and capacitors while improving droop response. Unfortunately, such converters utilize advanced digital CMOS processes with the maximum input voltage below 2 V. We propose a fully integrated linear regulator that enables doubling of the converter input voltage by properly biasing stacked drivers and bridge transistors. By implementing fast digital control the linear regulator meets the transient current demand of the converter without resorting to off-chip decoupling capacitors. In a 90 nm CMOS process, the 2.4V input, 1.2 V output, linear regulator occupies 0.03 mm2 for a plusmn1 A rating. A 288 ps response time and 97.5% current efficiency result in a 2.84times improvement in speed-power figure of merit over previous work